Efficiently querying dynamic XML documents stored in relational database systems. (18th July 2011) - Maghaydah, Moad; Orgun, Mehmet A.
Storing XML documents in relational database systems has become a widely used solution. However, in the process of shredding and indexing the XML document, the use of special labelling methods to recover the document order is still required in order to efficiently support data-centric queries and update operations (e.g., the addition and deletion of nodes from the document). In this paper, we present a new space-efficient labelling scheme based on Dewey codes. The new label structure, which is composed of parent-child components in the Dewey format, would significantly improve the performance of XML queries that are based on parent-child and sibling relationships. Furthermore, we introduce an alternative approach to validate ancestor relationships and to navigate upwards in XML trees efficiently. We report on an extensive experimental evaluation using several well-known XML benchmarks for the comparison of the impact of our approach on label length and query performance against those of some other recent Dewey-based approaches.